2013
DOI: 10.1007/s12088-013-0363-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Legionella spp. in Environmental Water Samples by ScanVIT-Legionella™ Method in Spain

Abstract: Rapid and more sensitive methods for the detection and quantification of viable Legionella cells have been developed. In this paper, a comparative analysis of environmental water samples using the ScanVIT-Legionella TM method and the traditional ''gold standard'' method of culturing is realised indicating the usefulness of the ScanVIT method. The ScanVIT-Legionella TM method was performed on environmental water samples from different locations of Huesca region (Spain). Legionella micro-colonies should appear g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Many factors may explain the low sensitivity rate of detection L. pneumophila by culture in water samples, such as: the presence of viable but non-culturable cells, loss of viability of bacteria after collection, and low concentration of legionellae in the samples [21]. Similar observations were reported by other authors [22] [23] [24]. The reason for the significant discrepancy between PCR and culture results for Legionella in water samples is the greater positivity rates for PCR than culture [25].…”
Section: Resultssupporting
confidence: 77%
“…Many factors may explain the low sensitivity rate of detection L. pneumophila by culture in water samples, such as: the presence of viable but non-culturable cells, loss of viability of bacteria after collection, and low concentration of legionellae in the samples [21]. Similar observations were reported by other authors [22] [23] [24]. The reason for the significant discrepancy between PCR and culture results for Legionella in water samples is the greater positivity rates for PCR than culture [25].…”
Section: Resultssupporting
confidence: 77%
“…Legionella pneumophila colonies appear red in color (Figure 2) on ScanVIT membrane, whereas those of other Legionella spp. would be in green color (Gruas et al, 2013). The detection of Legionella takes place on a cultivated filter brought into contact with the gene probes marked with a dye.…”
Section: Resultsmentioning
confidence: 99%
“…While L. longbeachae is generally isolated from soil, including potting soil [ 71 ], this microorganism has previously been isolated from water samples collected from hospital reticulation systems and cooling towers and is able to proliferate in Acanthamoeba polyphaga [ 72 74 ]. In addition, while L. pneumophila serotype 1 is responsible for most of the human reported infections, 17 additional species have also been associated with disease and these include L. longbeachae, L. micdadei , L. anisa and L. bozemanii [ 75 ]. BLAST analysis also revealed that L. norrlandica was of the dominant Legionella spp.…”
Section: Discussionmentioning
confidence: 99%